A Study On Financial Performance Analysis In Salem Steel Plant At Salem - KANAGARAJU, Dr. P.; SATHYA, S. (The journal of contemporary issues in business and government, 2021)
Today SAIL is one of the largest industrial entities in India. Its strength has been the diversified range of quality Steel product catering to the domestic, as well as the export market sandal large pool of technical and professional expertise. Today, the accent in Salem Authority of Indian Limited (SAIL) is to continuously adept to the competitive business environment and excel as a business organization, both within and outside in India. Hence, this study was undertaken to investigate into the financial performance of Salem Steel Plant at Salam District,Tamilnadu understand their performance in a highly competitive environment. The study revealed that Salem Steel Plant in the study area have not performed well on all the parameters of financial performance. On plant performed best on one parameter, but worst on another which prove that the overall financial performance of the steels has not been quite good and all the Steel Plants have to make improvements on different steels.